LANGUAGE, WESTERN MEN AND THAI WOMEN ON THE DATING SITE - Piayura, Orathai (PEOPLE: International Journal of Social Sciences, 2018)
This research studied the language of men on the Thai women dating site. The purpose of the study were 1) to investigate the kind of language being used by men on the dating site and 2) to study western men on the dating site’s social status. Data were collected from online dating sites randomly. There were 73 case studies for this research. The result of the study revealed that western men used a lot of positive adjectives to describe the desire characteristics of Thai women. They also used the pronoun ‘I’ and the possessive pronoun ‘My’ frequently. This illustrated the self-centric and the superiority feeling of men on the dating site. On the aspect of social status, the majority of these western men were divorced and middle-aged. They did not mention their occupation as if they found it not important for the relationship.